2019
DOI: 10.1001/jamanetworkopen.2018.7220
|View full text |Cite
|
Sign up to set email alerts
|

Association of Physician Group Participation in Accountable Care Organizations With Patient Social and Clinical Characteristics

Abstract: Key Points Question Are physician groups that care for socially and clinically vulnerable patients less likely to participate in accountable care organizations? Findings This cohort study of US physician groups from 2010 through 2014 found that groups participating in Medicare Shared Savings Program accountable care organizations cared for more clinically high-risk patients than did nonparticipating physician groups. There was no difference in patient socia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…1 Previous studies have noted discontinuities in specific disease or population subgroups. [2][3][4][5][6][7][8] This interrupted time series analysis and crosssectional study sought to quantify the magnitude of change in prevalence in all diagnostic categories for 3 widely used diagnostic classification systems and to explore potential reasons for these changes through selected clinical review.…”
Section: International Statistical Classification Of Diseases Tenth mentioning
confidence: 99%
See 1 more Smart Citation
“…1 Previous studies have noted discontinuities in specific disease or population subgroups. [2][3][4][5][6][7][8] This interrupted time series analysis and crosssectional study sought to quantify the magnitude of change in prevalence in all diagnostic categories for 3 widely used diagnostic classification systems and to explore potential reasons for these changes through selected clinical review.…”
Section: International Statistical Classification Of Diseases Tenth mentioning
confidence: 99%
“…To visualize patterns of observed changes, we created time series graphs for all diagnostic categories in each classification system. Each graph depicts 3 normalized series: (1) observed diagnostic category prevalence, (2) piecewise linear model predicted prevalence, and (3) locally estimated scatterplot smoothing curves, fit separately to the pretransition and posttransition periods. This last series helps to visualize possible nonlinear trends.…”
Section: Data Interpretation and Visualizationmentioning
confidence: 99%
“…An early, cross-sectional analysis using 2011 data found that ACO-attributed patients were less likely than non-ACO-attributed patients to be black, disabled, or vulnerable from the perspective of being Medicare/Medicaid dual-eligible (29). In contrast, a subsequent cohort study using longitudinal 2012-2014 data found that physician groups participating in the MSSP cared for more clinically high-risk patients and comparable numbers of socially vulnerable patients, as compared with nonparticipating physician groups (53). A separate observational analysis of MSSP ACOs demonstrated that patients with higher clinical risk scores were more likely than patients with lower risk scores to exit the program, a finding that suggests avoidance of high-risk patients could occur under ACOs (42).…”
Section: Unintended Consequences Of Population-and Episode-based Payment Models Health Care Disparitiesmentioning
confidence: 94%
“…16 However, the evidence that ACOs avoid vulnerable patients is inconsistent. Work has demonstrated that compared with nonparticipating groups, physician groups participating in the MSSP took care of a similar proportion of patients who are racial minorities, dually enrolled in Medicare and Medicaid, or living in a high-poverty zip code 17 and that ACOs with a high proportion of minority patients are committed to the mission of MSSP. 18 Accountable care organizations may worsen disparities even if physician groups care for similar proportions of socially vulnerable patients when they join the ACO if, once joining, physician groups reduce the share of vulnerable patients in their panels after joining an ACO, a practice known as cream-skimming.…”
Section: Introductionmentioning
confidence: 99%